Are first rib fractures a marker for other life-threatening injuries in patients with major trauma? A cohort study of patients on the UK Trauma Audit and Research Network database. Issue 4 (24th January 2017) - Sammy, Ian Ayenga; Chatha, Hridesh; Lecky, Fiona; Bouamra, Omar; Fragoso-Iñiguez, Marisol; Sattout, Abdo; Hickey, Michael; Edwards, John E
Abstract : Background: First rib fractures are considered indicators of increased morbidity and mortality in major trauma. However, this has not been definitively proven. With an increased use of CT and the potential increase in detection of first rib fractures, re-evaluation of these injuries as a marker for life-threatening injuries is warranted. Methods: Patients sustaining rib fractures between January 2012 and December 2013 were investigated using data from the UK Trauma Audit and Research Network. The prevalence of life-threatening injuries was compared in patients with first rib fractures and those with other rib fractures. Multivariate logistic regression was performed to determine the association between first rib fractures, injury severity, polytrauma and mortality. Results: There were 1683 patients with first rib fractures and 8369 with fractures of other ribs. Life-threatening intrathoracic and extrathoracic injuries were more likely in patients with first rib fractures. The presence of first rib fractures was a significant predictor of injury severity (Injury Severity Score >15) and polytrauma, independent of mechanism of injury, age and gender with an adjusted OR of 2.64 (95% CI 2.33 to 3.00) and 2.01 (95% CI 1.80 to 2.25), respectively. Risk-adjusted mortality was the same in patients with first rib fractures and those with other rib fractures (adjusted OR 0.97, 95% CI 0.79 to 1.19). Conclusion: First rib fractures are a marker of life-threatening injuries in major trauma, though they do not independently increase mortality. Management of patients with first rib fractures should focus on identification and treatment of associated life-threatening injuries.